EXAMINATION OF THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND COGNITIVE SKILLS - Gabriella Makra; László Balogh (University of Debrecen, Institute of Sport Sciences, 2021)
Introduction: Examining physical activity and cognitive function has become a popular topic of research since the quality of these two components influences our quality of life and performance. It is very important for both sexes, all ages and life situations. Objective: Determining a type of physical activity (PA) that has an effect on both cognitive functions (CF) and motor skills and performance. Clarifying or promoting measurement methods, or developing new methods that meet current standards and objectives. The results may be used to help to impove performance in all areas. Method: Primary purpose of our study was to conduct a review, in order to summarize the relevant literature on the following topics: sex, age, fitness level, possible illness. Conclusions: We found a significant relationship between cognitive functions and physical activity, which can be transposition in a proper way, both in terms of living standards and performance. On the other hand, there are a lack of uniform, accurate measurement methods. Thhere is a need for specific physical activity routines that specifically improve the level of cognitive function, even at an older age.